2019
DOI: 10.33788/rcis.65.2
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Residence Satisfaction of Elderly from Nursing Homes: Evidence from China

Abstract: With the aggravation of population aging, the problem of providing service for the aged has become the focus of the public. A large number of nursing homes have emerged under this background. Residence satisfaction is broadly used as the indicator to measure the quality of nursing homes. Focusing on the resident satisfaction formation from the organizational factors, this study investigate show staffi ng, hardware facilities, elderly service guarantee and perceived environment infl uence the satisfaction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Residence satisfaction is widely used as an indicator to measure the quality of nursing homes. Some of the factors related to the satisfaction of the elderly living in a nursing home include competent nursing home staff, services provided at the nursing home, guaranteed health care services received and the nursing home environment including facilities and infrastructure (11). The satisfaction of the elderly living in nursing homes will have an impact on their quality of life.…”
Section: Results and Discusionmentioning
confidence: 99%
“…Residence satisfaction is widely used as an indicator to measure the quality of nursing homes. Some of the factors related to the satisfaction of the elderly living in a nursing home include competent nursing home staff, services provided at the nursing home, guaranteed health care services received and the nursing home environment including facilities and infrastructure (11). The satisfaction of the elderly living in nursing homes will have an impact on their quality of life.…”
Section: Results and Discusionmentioning
confidence: 99%
“…(Cappelen et al, 2016;Mullan & Harrington, 2001;Vrotsou et al, 2021;Zhang & Wan, 2005). Additionally, influencing factors of psychological outcomes among nurses and residents were also examined in this field using SEM (Bratt & Gautun, 2018;Wan et al, 2019). The burst of keywords indicated that in addition to work engagement, job satisfaction, and burnout, nursing student is another emerging research hotspot in the near 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Já o terceiro artigo, de Wan et al (2019), buscou investigar como a equipe de funcionários, a infraestrutura física, a garantia de serviços para idosos e a percepção ambiental influenciam na satisfação dos moradores de casas de repouso. A avaliação envolveu 493 instituições de Shangai, China.…”
Section: » Factors In Residence Satisfaction Of Elderly From Nursing ...unclassified